Regularisation of singular 2D Fornasini-Marchesini models by output feedbacks - Kaczorek, Tadeusz (1932- ); Giang, Nguyen Bang (Zielona Góra: Uniwersytet Zielonogórski)
Necessary and sufficient conditions are established for regularisation of the singular 2D Fornasini-Marchesini model by an output feedback. Some procedures are presented for testing the regularity and regularisability of 2D models and for computation of the output feedback matrix. The procedures are illustrated by a numerical example.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka